Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To analyze the function [tex]\( g(x) = f(x + 4) \)[/tex] and determine the key feature associated with it, let's keep in mind that this function represents a horizontal shift of the original function [tex]\( f(x) \)[/tex] by 4 units to the left.
We'll examine each of the multiple-choice options to see if it describes the key feature of the function [tex]\( g(x) \)[/tex]:
A. [tex]$y$[/tex]-intercept at [tex]$(0, 4)$[/tex]:
- The [tex]$y$[/tex]-intercept of a function is the point where [tex]\( x = 0 \)[/tex]. For [tex]\( g(x) = f(x + 4) \)[/tex], the [tex]$y$[/tex]-intercept occurs at [tex]\( g(0) \)[/tex]. This means
[tex]\[ g(0) = f(4). \][/tex]
Without knowing the specific form of [tex]\( f(x) \)[/tex], we cannot definitively state that [tex]\( g(0) = 4 \)[/tex]. Hence, option A is not necessarily true.
B. horizontal asymptote of [tex]$y=4$[/tex]:
- Horizontal asymptotes are related to the values that a function approaches as [tex]\( x \)[/tex] tends to [tex]\(\pm\infty\)[/tex]. The transformation [tex]\( x \rightarrow x + 4 \)[/tex] in [tex]\( f(x + 4) \)[/tex] does not affect the horizontal asymptote. If [tex]\( f(x) \)[/tex] has a horizontal asymptote of [tex]\( y = L \)[/tex], then [tex]\( g(x) \)[/tex] also has the same horizontal asymptote [tex]\( y = L \)[/tex]. Hence, this option cannot be determined without knowing the behavior of [tex]\( f(x) \)[/tex].
C. [tex]$x$[/tex]-intercept at [tex]$(4, 0)$[/tex]:
- The [tex]$x$[/tex]-intercept for [tex]\( g(x) = f(x + 4) \)[/tex] occurs where [tex]\( g(x) = 0 \)[/tex]. If [tex]\( g(a) = 0 \)[/tex], then
[tex]\[ f(a + 4) = 0. \][/tex]
Setting [tex]\( b = a + 4 \Rightarrow b = 4 \)[/tex], [tex]\( f(4) = 0 \)[/tex]. No such information allows affirmatively stating that the intercept occurs at [tex]$(4, 0)$[/tex]. Hence, this option is generally not applicable without the specific intercepts of [tex]\( f(x) \)[/tex].
D. horizontal asymptote of [tex]$y=0$[/tex]:
- As previously noted, the horizontal transformation [tex]\( f(x + 4) \)[/tex] does not affect the asymptote of the function. Thus, if the original [tex]\( f(x) \)[/tex] has a horizontal asymptote of [tex]\( y = 0 \)[/tex], the function [tex]\( g(x) = f(x + 4) \)[/tex] will also have the same asymptote,
[tex]\[ \text{A horizontal asymptote at } y = 0. \][/tex]
Thus, the correct statement describing a key feature of the function [tex]\( g(x) = f(x + 4) \)[/tex] is option D: there is a horizontal asymptote of [tex]\( y = 0 \)[/tex].
We'll examine each of the multiple-choice options to see if it describes the key feature of the function [tex]\( g(x) \)[/tex]:
A. [tex]$y$[/tex]-intercept at [tex]$(0, 4)$[/tex]:
- The [tex]$y$[/tex]-intercept of a function is the point where [tex]\( x = 0 \)[/tex]. For [tex]\( g(x) = f(x + 4) \)[/tex], the [tex]$y$[/tex]-intercept occurs at [tex]\( g(0) \)[/tex]. This means
[tex]\[ g(0) = f(4). \][/tex]
Without knowing the specific form of [tex]\( f(x) \)[/tex], we cannot definitively state that [tex]\( g(0) = 4 \)[/tex]. Hence, option A is not necessarily true.
B. horizontal asymptote of [tex]$y=4$[/tex]:
- Horizontal asymptotes are related to the values that a function approaches as [tex]\( x \)[/tex] tends to [tex]\(\pm\infty\)[/tex]. The transformation [tex]\( x \rightarrow x + 4 \)[/tex] in [tex]\( f(x + 4) \)[/tex] does not affect the horizontal asymptote. If [tex]\( f(x) \)[/tex] has a horizontal asymptote of [tex]\( y = L \)[/tex], then [tex]\( g(x) \)[/tex] also has the same horizontal asymptote [tex]\( y = L \)[/tex]. Hence, this option cannot be determined without knowing the behavior of [tex]\( f(x) \)[/tex].
C. [tex]$x$[/tex]-intercept at [tex]$(4, 0)$[/tex]:
- The [tex]$x$[/tex]-intercept for [tex]\( g(x) = f(x + 4) \)[/tex] occurs where [tex]\( g(x) = 0 \)[/tex]. If [tex]\( g(a) = 0 \)[/tex], then
[tex]\[ f(a + 4) = 0. \][/tex]
Setting [tex]\( b = a + 4 \Rightarrow b = 4 \)[/tex], [tex]\( f(4) = 0 \)[/tex]. No such information allows affirmatively stating that the intercept occurs at [tex]$(4, 0)$[/tex]. Hence, this option is generally not applicable without the specific intercepts of [tex]\( f(x) \)[/tex].
D. horizontal asymptote of [tex]$y=0$[/tex]:
- As previously noted, the horizontal transformation [tex]\( f(x + 4) \)[/tex] does not affect the asymptote of the function. Thus, if the original [tex]\( f(x) \)[/tex] has a horizontal asymptote of [tex]\( y = 0 \)[/tex], the function [tex]\( g(x) = f(x + 4) \)[/tex] will also have the same asymptote,
[tex]\[ \text{A horizontal asymptote at } y = 0. \][/tex]
Thus, the correct statement describing a key feature of the function [tex]\( g(x) = f(x + 4) \)[/tex] is option D: there is a horizontal asymptote of [tex]\( y = 0 \)[/tex].
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.